(untitled) (Indian Journal Of Clinical Practice, 2026)
Gastroesophageal reflux disease (GERD) is a common and chronic acid-related disorder that significantly affects quality of life. Proton pump inhibitors (PPIs) remain the cornerstone of therapy, often prescribed in combination with prokinetics such as domperidone to enhance symptomatic relief. This survey aimed to assess physician perceptions, prescribing patterns, and key factors determining the choice of PPI–domperidone combinations in India. Methods: A cross-sectional, perception-based digital survey (Power Physician Survey 3.0) was conducted among 3,260 physicians across India. A structured questionnaire captured information on patient load, preferred treatment strategies, time to symptom relief, recurrence rates, and factors guiding the selection of specific PPI–domperidone combinations. Responses were analyzed using descriptive statistics. Results: Over half of the respondents (51.6%) preferred prescribing a PPI–domperidone combination rather than PPI monotherapy. The rabeprazole–domperidone (RD) combination emerged as the most preferred regimen (80.1%), primarily for its rapid acid inhibition (46.6%), better tolerability (18.3%), and cost-effectiveness (13%). About half of the physicians observed symptomatic relief within 2 to 3 days (50.6%), with 82.8% perceiving lower recurrence rates and 88.7% reporting improved patient adherence. On preference ranking, RD was selected as the first choice by 80.1% of physicians, followed by pantoprazole– domperidone (10.4%), omeprazole–domperidone (4.8%), and esomeprazole–domperidone (4.7%). The combination was also rated most effective for night-time heartburn (90%) and preferred for patients with comorbidities (86.3%). Conclusion: The findings highlight a strong real-world preference for the RD combination in GERD management, driven by its rapid action, safety, and patient-centered benefits including improved adherence, symptom control, and reduced recurrence. These insights emphasize the importance of balancing efficacy, tolerability, and affordability in clinical decision-making for acid-related disorders in India.